Enhancing students' higher-order thinking skills (HOTS) through an inductive reasoning strategy using geogebra - Misrom, Noor Suhaily (Kassel University Press GmbH, 2020)
The concept of Higher-Order Thinking Skills (HOTS) is one of the highlighted aspects in producing human capital of high quality. However, the level of HOTS among students in Malaysia is still at a lower stage. Among the causes of this problem is the learning strategy used in classroom, which is less effective in creating and enhancing HOTS optimally. Therefore, the main focus in this study was to investigate the potential role of an inductive reasoning strategy using Geogebra in increasing the students' level of HOTS. Besides, it also aimed to identify the relationship between HOTS and students' inductive reasoning for the topic of Graphs of Functions II. The design of study was quasi-experimental which involved 94 form-four students from a secondary school in Johor. The sample of this study was divided into three groups: (1) Treatment Group 1 (inductive reasoning strategy using Geogebra); Treatment Group 2 (inductive reasoning strategy); and (3) a control group (conventional). The instrument of the study comprised a set of HOTS questions and a worksheet based on an inductive reasoning strategy using Geogebra. Using the Multivariate Analysis of Variance (MANOVA), it was found that the overall HOTS level of the students, which included applying, analysing, evaluating and creating skills, could be enhanced through this strategy. The findings also show that there was a positive relationship between HOTS and inductive reasoning. In conclusion, an inductive reasoning strategy can provide positive impacts on students' HOTS in the topic of Graphs of Functions II.